2018
DOI: 10.1088/1757-899x/384/1/012065
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Transformer Conditions using Triangle Duval Method

Abstract: Electrical or thermal failure that occurred in the transformer oil can produce a dangerous gas called gas fault. By indicating the content of dissolved gases in the transformer oil, can be obtained information about what happened to the oil so it can be estimated indication of the type and cause of the failure in the transformer. The method used to identify and analyze the dissolved gases in oil is called Dissolved Gas Analysis (DGA). In this study conducted by the DGA Duval Triangle method for transformer oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The reduction in the number of gases to n=3 in the composition of 𝐢𝐻 4 , 𝐢 2 𝐻 2 , 𝐢 2 𝐻 4 is due to their status of a "key gas" in poorly classified situations of developing thermal defects in the ranges of low and medium temperatures. In addition, the indicated composition of gases determines the scheme for interpreting defects in PT using the Duval triangle method [26]- [28]. The analysis of the results showed that the reduction in the number of parameters involved in the formation of the Bayesian classification model causes a characteristic change in the statistical moments of the  ISSN: 2088-8708 RV 𝐷 in the classes of states 𝑆 1 , 𝑆 2 and.…”
Section: Calculation Results Analysis and Discussionmentioning
confidence: 99%
“…The reduction in the number of gases to n=3 in the composition of 𝐢𝐻 4 , 𝐢 2 𝐻 2 , 𝐢 2 𝐻 4 is due to their status of a "key gas" in poorly classified situations of developing thermal defects in the ranges of low and medium temperatures. In addition, the indicated composition of gases determines the scheme for interpreting defects in PT using the Duval triangle method [26]- [28]. The analysis of the results showed that the reduction in the number of parameters involved in the formation of the Bayesian classification model causes a characteristic change in the statistical moments of the  ISSN: 2088-8708 RV 𝐷 in the classes of states 𝑆 1 , 𝑆 2 and.…”
Section: Calculation Results Analysis and Discussionmentioning
confidence: 99%
“…This study presents the development of using multi-method DGA interpretation from the combination of duval triangle and duval pentagon method with improvement from previous research. On the [6] duval triangle method can identify partial discharge and thermal failure, and from [9] the duval pentagon are use for base method for interpretation. In the result section, the duval triangle show the discharge and thermal faults to often be the identification result, but the duval pentagon may be more sensitive for identification of stray gassing.…”
Section: Mixture Of Faults Identificationmentioning
confidence: 99%
“…Several studies have been carried out to reduce misinterpretation and detect mixture of faults. A study in reference [6] uses the Duval triangle method for identification of thermal failure and partial discharge of transformer oil used in geothermal power plant UPJP Kamojang. A study in [7] proposed the integration of Duval Pentagon to the multi-method interpretation to improve the accuracy of dissolved gas analysis technique.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been carried out using the Duval Triangle and Pentagon methods in interpreting transformer conditions, in reference [9] using the Duval Triangle method in examining the conditions of the Kamojang UPJP transformer. Then in [10] developing an Artificial Neural Network (ANN) model based on Duval Pentagon method in improving diagnostic and monitoring capabilities of transformers.…”
Section: Introductionmentioning
confidence: 99%